Plan for the Neutron Irradiation Experimental Instruments - Inagaki, Makoto; Takamiya, Koichi (RADIOISOTOPES, 2025)
At the neutron irradiation experimental instruments in research reactors, experiments such as neutron activation analysis, Ar/Ar dating, and radioisotope production can be carried out. This article describes the plans for the instruments to conduct these experiments in the new research reactor at the Monju site.